Psychological Conflict in A Dystopian World in Ray Bradbury’s Fahrenheit 451: A Psychoanalytic Study of The Main Characters - Nada Khitbatul Padilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Ray Bradbury’s Fahrenheit 451 is a landmark dystopian novel that critiques extreme social control through technology, censorship, and propaganda while exploring its profound psychological impact on individuals. The research aims to explore the psychological dimensions of the dystopian world in Ray Bradbury’s Fahrenheit 451, particularly the psychological conflicts experienced by the novel’s main characters, Guy Montag and Mildred Montag. Freud’s psychoanalytic theory is used to investigate the relationship between the id, ego, and superego in the main characters of the novel. This shows that Montag experiences psychological changes due to the conflict between the id, ego, and superego, which leads him from obedience to freedom of thought, supported by the process of sublimation. In contrast, Mildred shows psychological stagnation with an overpowering superego and a repressed id through denial, which leads her to be trapped in emotional alienation. This study emphasizes psychoanalysis as well as social critique, highlighting Fahrenheit 451's relevance to contemporary challenges of freedom and individuality.